Good Corporate Governance Dan Environmentalal, Social, Governance Disclosures Di Indonesia - Lailah Fujianti; Nelyumna Nelyumna; Widyaningsih Azizah; Sinta Budi Astuti; Nurul Hilmiyah; Anninsa Lailatul Qodriyah (Universitas Muhammadiyah Malang, 2024)
Purpose: This research aims to confirm the roles of Good Corporate Governance (GCG) and Environmentalal, Social, Governance (ESG) Disclosures in Indonesia. Methodology/approach: The research method employed is a quantitative approach using secondary data. The sample was selected using purposive sampling, resulting in 161 manufacturing companies listed on the Indonesia Stock Exchange in 2021. The research analysis technique utilizes multiple linear regression. Findings:The research results reveal a significant positive role of the Board of Commissioners and Independent Board of Commissioners in ESG disclosure, whereas the Audit Committee does not play a significant role in ESG. Practical implications: The number of members in the Board of Commissioners and Independent Board of Commissioners can stimulate an improvement in ESQ disclosure. However, the presence of the Audit Committee has not been able to demonstrate a role because Indonesian companies form an audit committee merely to comply with existing regulations. Originality/value: The limited research examining Environmentalal, Social, Governance Disclosures in Indonesia has been identified. Previous research results indicate that the variable playing a significant role in promoting disclosure improvement is Good Corporate Governance (GCG). Therefore, this study further investigates the role of GCG in enhancing ESQ disclosures.